Evidence-based medicine in primary care: some views from the 3rd U.K. workshop on teaching evidence-based medicine. Issue 5 (October 1997) - Lipman, Toby; Rogers, Stephen; Elwyn, Glyn Jones
Abstract : The past year has seen much debate about evidence-based medicine, some of it very heated (1). Although such writers as Dawes (2) and Ridsdale (3) have discussed the place of evidence based medicine in general practice, it is still unclear what its consequences will be for primary care clinicians and their patients.